Advanced biology - "John, Mary and Jones, Geoff" (Cambridge University Press: Cambridge, 1997)
The text contains clear explanations of facts and concepts, with a controlled language level to ensure accessibility for A-level students, including those for whom English is a second language. Applications of biology to industry and medicine are shown.
Keywords: Biology - Textbook